2016
DOI: 10.1371/journal.pone.0147430
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Adenosine Uptake and Its Contribution to Signaling that Mediates Profibrotic Activation in Renal Tubular Epithelial Cells: Implication in Diabetic Nephropathy

Abstract: Altered nucleoside levels may be linked to pathogenic signaling through adenosine receptors. We hypothesized that adenosine dysregulation contributes to fibrosis in diabetic kidney disease. Our findings indicate that high glucose levels and experimental diabetes decreased uptake activity through the equilibrative nucleoside transporter 1 (ENT1) in proximal tubule cells. In addition, a correlation between increased plasma content of adenosine and a marker of renal fibrosis in diabetic rats was evidenced. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Interestingly, A 2B receptor expression in non-diabetic CKD exhibited a similar upregulated pattern (Zhang et al 2013). For the A 3 receptor the most remarkable feature was receptor distribution at the tubules and interstitium during the advanced state of the diabetic kidney disease, which was recently recognized by Kretschmar et al (2016).…”
Section: Pathogenic Functions Of Adenosine Receptors In Ckdmentioning
confidence: 83%
See 3 more Smart Citations
“…Interestingly, A 2B receptor expression in non-diabetic CKD exhibited a similar upregulated pattern (Zhang et al 2013). For the A 3 receptor the most remarkable feature was receptor distribution at the tubules and interstitium during the advanced state of the diabetic kidney disease, which was recently recognized by Kretschmar et al (2016).…”
Section: Pathogenic Functions Of Adenosine Receptors In Ckdmentioning
confidence: 83%
“…Roa et al (2009) using this same animal model showed that isolated glomeruli from diabetic rats contained significantly higher external adenosine compared to controls (37.4 ± 3.1 v/s 6.0 ± 0.6 nM, corrected per µg of total glomeruli protein). Further, it was recently demonstrated that renal injury progression in diabetic rats develops with increased adenosine levels, having a strong correlation with the profibrotic marker α-SMA (Kretschmar et al 2016), meanwhile increased urinary adenosine excretion could be detected during early onset of kidney dysfunction (Oyarzún et al 2016). These observations highlight the fact that locally generated adenosine contributes to setting the pathological milieu of CKD progression.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
See 2 more Smart Citations
“…This increase correlated with a marker of renal fibrosis in diabetic rats. Furthermore, the expression of profibrotic cell activation markers α‐smooth muscle actin and fibronectin was increased by stimulation of A 3 receptors (Kretschmar et al , ) (Figure ).…”
Section: Pathological Role Of Adenosine In Diabetesmentioning
confidence: 96%